Safe PN Practices - Bittner, Dennis (MD Conference Express, 2015)
Clinical guidelines and consensus recommendations from A.S.P.E.N. to assure the safe use of PN are not always properly implemented in clinical practice by nutrition support clinicians. Elimination of these practice gaps was the subject of a 3-speaker session at Clinical Nutrition Week.